Newer Forms of Tobacco Products: Characteristics of Poly Users Among Adults Living in Colorado—A Secondary Data Analysis of the Attitudes and Behaviors Survey on Health 2015. (September 2019) - El Hajj, Dana; Cook, Paul F; James, Katherine A; Battaglia, Catherine; Prochazca, Allan V
Aims: Data from The Attitudes and Behaviors Survey (TABS) conducted in 2015 were used to investigate the prevalence of different forms of tobacco use and marijuana use among adults in Colorado. Methods: A secondary analysis of TABS on health data was conducted. A representative sample of 8616 adults 18 years and older participated in the survey, with sample weights used to adjust for oversampling. Results: Lifetime prevalence of cigarette-only use was 25.8%, compared with 10.6% for hookah use, 7.0% for both hookah and cigarettes, 12.6% for anything except cigarettes, and 43.0% for marijuana. The typical hookah user was a single/living alone (15.9%), English-speaking (11.6%), male (16.7%), age < 30 years (24.2%), with some college education (13.0%), and income less than 35 000 per year (14.3%). Hookah users, whether or not they also used cigarettes, were similar to those who used any other noncigarette tobacco products. The typical marijuana user was a single/living alone (50.2%), white (46.0%), English-speaking (46.7%), male (48.5%), age < 30 years (50.1%), with a graduate degree (40.8%) and salary of at least 50 000 per year (43.4%). Implications: In Colorado, in 2015, cigarette use was still highest among all forms of tobacco, but the use of other tobacco products such as vaping and hookah is on the rise, especially among young adults. Marijuana and hookah users were demographically similar to each other, and different from the typical cigarette user. These results indicate the need for further study of alternative tobacco product use, especially among young adults.